EFFECTS OF EXTERNAL FACTORS ON THE SMALL AND MEDIUM ENTERPRISES IN SOUTH SUMATERA PROVINCE, INDONESIA - Jeffrey Tange (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2015)
Small and medium enterprises are known to be major contributors to the economy of South Sumatra. However, the support they receive from government and other stakeholders are insufficient to the size of the sector. This paper examines the effects of external macroeconomic and social factors such as credit, education, tax and inflation on small and medium enterprises employment in South Sumatra. Secondary time series data from 1995 to 2014 was used for this research. The data was stabilized by first differencing then ordinary least squares method was applied to analyze the data. The results show that tax had strong negative influence on the SMEs employment at five percent significance level. Credit and education also had some impact on SMEs at ten percent significance level. However, their coefficients showed negative signs reflecting the negative growth of SMEs over the period. This meant that, despite the increases in credit received by SMEs and the primary and secondary school graduates entering the SME sector, the SME employment declined over the period. There was no significant influence on the SMEs by inflation over the period studied though the coefficient of inflation showed a positive sign disclosing that inflation had no negative impact on SME employment over the period covered.